Diels–Alder Reactions of 2-Vinylindoles with Cyclic Dienophiles: Synthesis of [c]-Annulated Tetrahydrocarbazoles - Pirovano, Valentina; Abbiati, Giorgio; Dell’Acqua, Monica; Facoetti, Diego; Giordano, Mara; Rossi, Elisabetta (Synlett, 2012)
Diels–Alder reactions of 2-vinylindoles with cyclic carbo- and heterodienophiles, in the presence of suitable Lewis acids, led to uncommon [c]-carbo- and furoannulated tetrahydrocarbazoles. The obtained compounds encompass a carbonyl group in an angular position, suitable for further transformations, and represent useful intermediates for the synthesis of more complex structures.
Keywords: Diels–Alder reaction; heterocycles; polycycles; Lewis acids; indoles